Knowledge and Attitude towards Contraceptive use among Adolescents in Senior High School in the Ledzokuku-Krowor Municipality. - Akuffo, A.D. (University of Ghana, 2018)
Background: Contraceptive use among adolescents is relatively high. This is crucial in view of the fact that a nation‟s growth and development depend largely on the current wellbeing of its adolescents. This study therefore, sought to explore the level of knowledge and attitudes of adolescent towards contraceptive use within the Ledzokuku Krowor Municipality within the Greater Accra region. Methodology: The study is a cross-sectional study using qualitative method and used in-dept interview (IDI) for data collection. The study used senior high school students and parents in the municipality. A purposeful sampling technique was used to select respondents for the study. The data collected from respondents were transcribed and analyzed using thematic content analysis. Results: Findings from the study revealed that majority of adolescents had an appreciable knowledge about contraceptive use, and their sources of knowledge about contraceptives emanated from parents, peers and the mass media. It was also revealed that majority of adolescents within the Ledzokuku Krowor of the Greater Accra region advocated for the use of contraceptives because of the following reasons: prevention of unwanted pregnancies, avoiding the contraction of sexually transmitted diseases and, prevents the adolescents from incurring huge financial burdens especially among female adolescents. Also, most parents considered the provision of reproductive health education to their adolescent children as a priority area for them for shaping and modeling their sexual life. Conclusion: Adolescents within the Ledzokuku Krowor Municipality thus far have divided positions to contraceptive use owing to the myths and misconceptions associated with its use. Multiple factors such as societal ridicule, stigmatization from friends, and parental rejection of its use contribute significantly to adolescents‟ attitude towards contraceptive use. It is therefore, important for collaborations and partnerships between the Ghana Health Service and the Ghana Education Service to intensify public education among adolescents about contraceptive use in order reduce the rate of sexually transmitted diseases and unwanted pregnancies within that age cohort of the country.
MPH.
Keywords: Contraceptive; Adolescents; Senior High School; Ledzokuku- Krowor Municipality